1208. Impact of Admission to an Inpatient Infectious Disease Unit on Methicillin-Resistant Staphylococcus aureus Bloodstream Infections. (26th November 2018) - Mirza, Zainab Farooqui; Bardossy, Ana C; Misikir, Helina; Hadid, Hind; Baratz, Nathalie; Rizvi, Hira; Herc, Erica; Chen, Anne; Zervos, Marcus
Abstract: Background: Methicillin-resistant Staphylococcus aureus (MRSA) blood stream infection (BSI) remains a condition with high mortality. Despite the introduction of new antibiotics, the mortality in the past 10 years at our institution remains unchanged. To evaluate measures that improve outcomes in these patients (patients), we studied the impact of admission to an inpatient infectious disease (ID) unit. Methods: We identified a retrospective cohort of patients with MRSA BSI at an 800-bed hospital in urban Detroit from January 2013 to February 2017. Patients were assigned to one of the three groups: group 1 was admission to inpatient ID unit where the ID doctors were the attending physicians, group 2 was ID consultation (without admission to ID unit), and group 3 was no ID consultation. Demographics, clinical information, and 30 day mortality from index blood culture were collected. Source of BSI was classified into four categories: primary (endovascular infection); secondary (respiratory, skin, osteomyelitis, abdominal and genitourinary infections); central line associated; unknown. Unpaired t-test and Fisher's exact test were used to compare groups. Results: A total of 477 patients were identified with MRSA BSI during the study period. 89 (18.7%) were in group 1, 299 (62%) in group 2 and 89 (18.7%) in group 3. Pt clinical characteristics and outcomes are shown in Table 1. Overall 30-day mortality was 21.4%. Comparison of mortality between groups are shown in Table 2. Conclusion: While it is well established that ID consultation has improved outcomes in MRSA BSI, this is the first study that shows that admission to an inpatient ID unit decreases mortality even further. Disclosures: All authors: No reported disclosures.